EU climate countdown: economic risks, adaptation and smart policies - Ana-Elena Varadi; Oana-Ramona Lobont; Sorana Vatavu (International Journal of Climate Change Strategies and Management)
Purpose – This paper aims to analyse the impact of various climate change indicators on economic growth while further scrutinising the overall efficiency of environmental policies adopted at the European Union (EU) level. The paper considers the European Green Deal policy framework as a prism for assessing whether an increase in environmental expenditure mitigates climate change. Design/methodology/approach – Given the duality of the study, this paper examines the immediate impact of climate change on economic growth by using multiple linear regression and evaluates the effectiveness of environmental policies through a multiple indicators multiple cause (MIMIC) Model. As the paper assesses the policy efficiency in EU countries, this paper has used various climate and economic-related indicators from all 27 EU member states for a period of 12 years (2010–2021). Findings – The results suggest that the macroeconomic environment is indeed impacted by climate change mechanisms, particularly through industrial activity that leads to pollution and resource depletion. Furthermore, through the MIMIC model approach, the results display that environmental expenditures have also diminished the risks associated with climate change indicators, especially in reducing greenhouse gas emissions. Originality/value – This paper provides a clear overview of the manner in which climate change risks affect economic growth and, in turn, how EU countries are mitigating such risks. It proposes a traditional yet controversial method for assessing the correlation between indicators and corresponding causes whilst also considering various indicators to explain the means through which the EU Commission had applied its adopted environmental policies to mitigate environmental risks.